THE INSTRUCTIONAL DOCUMENTS OF THE MILITARY GOVERNOR OF THE TURGAI REGION A. GEINS AS A HISTORICAL SOURCE (Journal of history, 2025)
The purpose of the study is to identify the specific methods of administration in the Turgai region in 1870-1890s at the level of local administration (district chief, volost, aul headman) through the adopted and implemented instructions. The studied Instructions reflected how adapted the colonial bureaucratic apparatus at the local level in the implementation of reforms of the second half of the 19th century. The methodology of the study was the concept of new imperial history. The research is based on the principle of historicism, objectivity and systematicity. Result. The Russian Empire, expanding its borders to the East, aimed to bring the native population of the same Turgai region to the so-called “all-Russian citizenship”, with the desirability of expanding the Russian language in office work, with the transition to all-Russian laws in the future. The analysis of instructional documents allows us to assert that a symbiosis of the service and paternalistic model of the state can be traced.  The uyezd chiefs were instructed to work for the benefit of their subordinates and for their substantial benefit, to ensure private and public rights of Kazakhs, to protect their peace. At the same time, it was argued that not volosts, but uyezd chiefs should become the masters of the uyezd and have power among the native population.
Keywords: empire, administration, Uyezd chiefs, Temporary Instruction, Motivated Instruction, Turgai region.